2007
DOI: 10.1111/j.1600-0854.2007.00619.x
|View full text |Cite
|
Sign up to set email alerts
|

Mucolipin‐2 Localizes to the Arf6‐Associated Pathway and Regulates Recycling of GPI‐APs

Abstract: In mammals, the mucolipin family includes three members mucolipin-1, mucolipin-2, and mucolipin-3 (MCOLN1-3). While mutations in MCOLN1 and MCOLN3 have been associated with mucolipidosis type IV and the varitint-waddler mouse phenotype, respectively, little is known about the function and cellular distribution of MCOLN2. Here we show that MCOLN2 traffics via the Arf6-associated pathway and colocalizes with major histocompatibility protein class I (MHCI) and glycosylphosphatidylinositol-anchored proteins (GPI-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
100
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 39 publications
3
100
0
Order By: Relevance
“…Recent studies have demonstrated that the KK 3114 Journal of Cell Science 123 (18) mutations in TRPML2 and TRPML3 exert a dominant-negative inhibitory effect on the function of their respective native channels. This effect was attributed to the interactions of TRPML2-KK and TRPML3-KK with and neutralization of the activity of their corresponding native channel (Karacsonyi et al, 2007;Kim et al, 2009). In a similar manner, we hypothesized that if the TRPML(P) and TRPML(P-KK) mutants were to form channel assemblies with each other, regardless of channel identity, then the channel-inactive TRPML(P-KK) mutants should exert a dominant-negative effect on constitutively active TRPML(P) mutants by rendering the complex inactive.…”
Section: +mentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have demonstrated that the KK 3114 Journal of Cell Science 123 (18) mutations in TRPML2 and TRPML3 exert a dominant-negative inhibitory effect on the function of their respective native channels. This effect was attributed to the interactions of TRPML2-KK and TRPML3-KK with and neutralization of the activity of their corresponding native channel (Karacsonyi et al, 2007;Kim et al, 2009). In a similar manner, we hypothesized that if the TRPML(P) and TRPML(P-KK) mutants were to form channel assemblies with each other, regardless of channel identity, then the channel-inactive TRPML(P-KK) mutants should exert a dominant-negative effect on constitutively active TRPML(P) mutants by rendering the complex inactive.…”
Section: +mentioning
confidence: 99%
“…Furthermore, recombinant as well as native TRPML channels also physically interact with each other in homo-and heteromultimeric combinations (CurcioMorelli et al, 2010;Venkatachalam et al, 2006;Zeevi et al, 2009). In addition, TRPML2 and TRPML3 traffic, in part, to lysosomes (Karacsonyi et al, 2007;Kim et al, 2009;Martina et al, 2009;Zeevi et al, 2009) where, like TRPML1, they also appear to regulate lysosomal function, in an as-yet-unknown manner. Indeed, gene-specific knockdown of TRPML2 or TRPML3 leads to lysosomal inclusions reminiscent of those found in MLIV patient TRPML1-null cells (Zeevi et al, 2009), suggesting that TRPMLs might dynamically interact with each other to sustain lysosomal integrity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, ADP-ribosylation factor 6 (Arf6)-dependent endocytosis has been shown to traffic GPI-linked proteins (Karacsonyi et al, 2007), such as the CVB3 co-receptor DAF. Arf6-mediated endocytosis is a lipid-raft and non-raft endocytosis pathway that cycles at the plasma membrane and is involved in the recycling of major histocompatibility complex class I to and from the cell surface.…”
Section: Introductionmentioning
confidence: 99%